Insulation characteristic evaluation method for C4F7N gas in high-voltage insulation device
By using SnSe materials in high-voltage insulation devices to evaluate the adsorption capacity and conductivity of C4F7N gas decomposition products, the problem that the decomposition characteristics and effects of C4F7N gas under high pressure have not been fully revealed has been solved, and the health status of high-voltage insulation devices has been realized. Diagnosis and early warning of insulation faults.
Patent Information
- Application Number
- CN202411512952.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-28
AI Technical Summary
C4F7N gas may decompose and generate a variety of gas products in high-pressure insulating devices, affecting the insulation characteristics and reducing the safety of the device. The prior art has not fully disclosed its decomposition characteristics and influence under high pressure.
By importing the initial parameters of SNSE materials in the Materials Studio material library, establishing its minimum crystal cell structure, and performing geometric optimization and energy calculations, the molecular model of C4F7N gas decomposition products, building an absorbent, doped energy, and charge transfer amount The calculation function is calculated by the density general letter theory to evaluate the adsorption capacity and conductivity of the SNSE layer to the C4F7N decomposition product.
It achieves accurate assessment of C4F7N gas decomposition products in high-voltage insulation devices, can diagnose the health status of the device, and provide early warning of insulation faults, providing new ideas for online monitoring and fault diagnosis technology.
Smart Images

Figure CN119339855A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high voltage electricity and insulation, and in particular relates to a method for evaluating the insulation characteristics of C4F7N gas in a high voltage insulation device. Background Art
[0002] Sulfur hexafluoride (SF6) has long been widely used in high-voltage electrical equipment such as gas-insulated substations due to its excellent insulation and arc-extinguishing capabilities. However, as a greenhouse gas, SF6 has a much higher greenhouse effect potential than CO2. Therefore, with increasingly stringent environmental regulations, research on alternatives to SF6 has become increasingly urgent.
[0003] As a potential environmentally friendly alternative gas, C4F7N has gradually attracted widespread attention due to its low global warming potential and good insulation properties.
[0004] However, the application of C4F7N in high-voltage insulation devices still faces many technical bottlenecks, such as its insulation performance, breakdown characteristics, and the impact of decomposition products that may be produced in the insulation state on the stability and safety of the equipment still need to be studied. In particular, C4F7N may decompose into a variety of gas products under the action of an electric field, and these decomposition products may affect the insulation properties and thus the safety of the device. Therefore, studying the decomposition products of C4F7N and their impact on insulation performance is the key to evaluating the application potential of C4F7N.
[0005] By monitoring the decomposition products of C4F7N, the health status of high-voltage equipment can be effectively diagnosed, thereby achieving early warning of insulation failure. Therefore, the study of the gas-sensitive properties of C4F7N decomposition products will help develop online monitoring and fault diagnosis technologies. However, current research on C4F7N is mostly focused on basic insulation performance testing, and its decomposition characteristics under high voltage and the effects of the various gases it generates on the insulation system have not been fully revealed. Whether these decomposition products will accumulate in the equipment or have a negative impact on the long-term reliability of the system requires further exploration. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for evaluating the insulation characteristics of C4F7N gas in a high-voltage insulation device. The insulation characteristics evaluation method provided by the present invention can accurately evaluate the influence of the sensing material on the decomposition products and insulation performance of C4F7N, thereby effectively diagnosing the health status of the high-voltage insulation device and realizing early warning of insulation faults, which provides a new idea for accurate diagnosis and online monitoring of insulating environmental protection gas in high-voltage insulation devices.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for evaluating the insulation properties of C4F7N gas in a high-voltage insulation device, comprising the following steps:
[0009] (1) The initial parameters of the SnSe material were imported from the Materials Studio material library. After cutting the (001) crystal plane, the minimum unit cell structure of the SnSe layer was established.
[0010] (2) After geometric optimization of the SnSe layer, the system energy and charge conditions of the SnSe layer are determined.
[0011] (3) A molecular model of the decomposition products of C4F7N gas was established, and the geometry of the decomposition products of C4F7N gas was optimized to determine the system energy, charge status, bond lengths and bond angles of each molecule of the SnSe layer.
[0012] (4) Geometric optimization and energy calculation of the single-chain adsorption structure of C4F7N gas decomposition products.
[0013] (5) Construct the calculation functions of the adsorption energy, doping energy and charge transfer amount of the SnSe layer, and define the required calculation formulas and physical quantities.
[0014] (6) Set the parameters of the custom adsorption calculation formula and construct a density functional theory calculation model of SnSe based on a 7×7×1 Monkhorst-Pack k-point grid.
[0015] (7) The adsorption models of C4F7N gas decomposition products were established at the top, hole and bridge positions of Sn and Se atoms on the surface of the SnSe layer. Then, according to the overall energy and charge transfer of each adsorption structure, the SnSe-based composite adsorption structure with the smallest deformation of the SnSe layer, the largest charge transfer amount and the largest adsorption energy for different target molecules was found in combination with a custom adsorption calculation formula.
[0016] (8) The density of states of the decomposition products of SnSe and C4F7N gases were derived and analyzed. Then, the conductivity of the adsorption system was analyzed based on the integral and variation degree of the energy curve near the Fermi level.
[0017] (9) Calculate the change in the work function of the SnSe adsorption system in the decomposition products of C4F7N gas.
[0018] (10) The recovery time τ is used to evaluate the ability of SnSe materials to desorb gas, which is used to evaluate the effectiveness of high-voltage insulation devices and to evaluate the gas sensing ability of the SnSe layer.
[0019] The insulation property evaluation method provided by the present invention can accurately evaluate the influence of the sensing material (i.e., SnSe material) on the decomposition products and insulation performance of C4F7N, thereby effectively diagnosing the health status of the high-voltage insulation device and realizing early warning of insulation faults, which provides a new idea for accurate diagnosis and online monitoring of insulating environmental protection gas in high-voltage insulation devices.
[0020] It should be noted that the "7×7×1 Monkhorst-Pack k-point grid" is a parameter setting expression used for Brillouin zone sampling when performing first-principles calculations in fields such as materials science and physics.
[0021] The specific meanings are as follows:
[0022] Monkhorst-Pack method: This is a method for selecting discrete k points in reciprocal space (Brillouin zone). The purpose is to sample the Brillouin zone as efficiently as possible while ensuring the accuracy of the calculation to obtain relevant information such as the electronic structure of the material. This method is widely used in first-principles calculations such as density functional theory (DFT).
[0023] Specific parameters of 7×7×1: The three numbers here correspond to the number of k-point divisions in three directions (usually the three coordinate axis directions of three-dimensional crystals). For "7×7×1", it is divided into 7 parts in two dimensions (such as the plane direction of the crystal), that is, 7×7 k-points are selected; and in the third dimension (such as the vertical direction of the crystal), it is only divided into 1 part, that is, only 1 k-point is selected. This asymmetric division is usually determined according to the structural characteristics of the crystal and the calculation requirements. For example, if the periodicity of the crystal in a certain direction is weak or the physical properties in this direction have little effect on the whole, fewer k-points can be selected in this direction to reduce the amount of calculation while ensuring the accuracy of the calculation results.
[0024] In summary, the 7×7×1 Monkhorst-Pack k-point grid is a way to sample the Brillouin zone of a crystal under a specific calculation method. In this way, information such as the electronic structure of the crystal can be effectively obtained in first-principles calculations, providing a basis for studying the physical properties of materials.
[0025] Preferably, after the geometry optimization of the SnSe layer in step (2), a Sn on the surface of the SnSe layer is firstly removed to form a vacancy structure and then the geometry optimization is performed, and then the system energy and charge of the SnSe layer are determined.
[0026] Preferably, when the molecular model of the C4F7N gas decomposition product is established in step (3), a model of a single transition metal atom is also established; when the geometry optimization of the C4F7N gas decomposition product is performed in step (3), the geometry optimization of the single transition metal atom is also performed.
[0027] Preferably, the transition metal atoms include Ni atoms.
[0028] Preferably, between step (6) and step (7), the following steps are performed:
[0029] The geometrically optimized single Ni atom is placed at a Sn vacancy of a SnSe layer to form a Ni-SnSe layer, and then the Ni-SnSe layer is geometrically optimized again.
[0030] In the present invention, Ni atoms and the SnSe layer of Sn vacancies can form reliable chemical bonds, and produce obvious orbital hybridization with the decomposition products of C4F7N gas during the adsorption process, so that the adsorption capacity of the SnSe layer can be significantly improved and optimized, and the theoretical recovery time and work function of the SnSe material at room temperature are significantly improved.
[0031] Preferably, the C4F7N gas decomposition products in step (3) include CF3CN, COF2 and C2F5CN.
[0032] Preferably, when the adsorption model of the C4F7N gas decomposition product is established in step (7), the distance between the C4F7N gas decomposition product and the SnSe layer is controlled within For example it could be or wait.
[0033] Preferably, after step (7), the adsorption energy calculation formula of the C4F7N gas decomposition product on the SnSe layer is obtained:
[0034] E Ads =E Gas / SnSe -E SnSe -E Gas .
[0035] Among them, E Gas / SnSe is the energy of the decomposition product of C4F7N gas adsorbed by the SnSe layer, E SnSe is the energy of the SnSe layer, E Gas is the energy of the decomposition product of a single C4F7N gas.
[0036] Preferably, after step (7), the charge transfer amount Q of the SnSe adsorption system is obtained. Tra =Q a -Q b .
[0037] Among them, Q a is the charge carried by the SnSe layer after adsorbing the decomposition product of C4F7N gas, Q b is the charge carried by the SnSe layer before adsorbing the decomposition products of C4F7N gas.
[0038] Preferably, the formula used in step (9) to calculate the change in the work function of the SnSe adsorption system in the C4F7N gas decomposition product is:
[0039]
[0040] Among them, E vacuum is the potential away from the surface of the SnSe layer, and E fermi is the energy of the highest occupied state in the system.
[0041] It should be noted that the work function (WF) is defined as the energy required for an electron to escape from the surface of a material.
[0042] It should be noted that the above-mentioned system refers to a doping system and an adsorption system.
[0043] In the present invention, the work function can be used to further analyze the adsorption characteristics of the SnSe adsorption system, and the influence of transition metal atom doping on the surface electronic properties of the SnSe material and its interaction with gas molecules can be revealed.
[0044] Preferably, the calculation formula of the recovery time τ in step (10) is:
[0045] τ=v0 -1 exp(-E a / kT).
[0046] Among them, v0 -1 is the trial frequency, which is 10 12 s -1 ; k is 1.38×10 -23 J / K; T is the actual temperature, the unit is K.
[0047] It should be noted that the recovery time τ refers to the time required for the gas to return from the adsorbed state to the original state.
[0048] The present invention can predict the response speed and recovery ability of the material in the sensing process by calculating the recovery time τ, and is helpful to optimize material selection and sensor design, making actual experiments more targeted and efficient.
[0049] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] The insulation property evaluation method provided by the present invention can accurately evaluate the influence of the sensing material (i.e., SnSe material) on the decomposition products and insulation performance of C4F7N, thereby effectively diagnosing the health status of the high-voltage insulation device and realizing early warning of insulation faults, which provides a new idea for accurate diagnosis and online monitoring of insulating environmental protection gas in high-voltage insulation devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The front view and the left view of the SnSe layer provided in a specific embodiment of the present invention after 7×7×1 Monkhorst-Pack k-point grid geometry optimization.
[0053] Figure 2 This is a geometric model of a SnSe layer after adsorbing C4F7N gas decomposition products provided in a specific embodiment of the present invention.
[0054] Figure 3 Schematic diagram of theoretical recovery time of SnSe layer during adsorption of C4F7N gas decomposition products provided in a specific embodiment of the present invention.
[0055] Figure 4 The front view and the left view of the Ni—SnSe layer provided in a specific embodiment of the present invention after 7×7×1 Monkhorst-Pack k-point grid geometry optimization.
[0056] Figure 5 This is a geometric model of a Ni-SnSe layer after adsorbing C4F7N gas decomposition products provided in a specific embodiment of the present invention.
[0057] Figure 6 The state density distribution diagram of the decomposition products of C4F7N gas adsorbed by the SnSe layer and the Ni-SnSe layer respectively provided in a specific embodiment of the present invention.
[0058] Figure 7 The work function variation curves of the SnSe layer and the Ni-SnSe layer in the C4F7N gas decomposition products provided in a specific embodiment of the present invention are shown.
[0059] Figure 8The theoretical recovery time of the Ni-SnSe layer during the adsorption of C4F7N gas decomposition products provided in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0061] In a specific embodiment, the present invention provides a method for evaluating the insulation properties of C4F7N gas in a high-voltage insulation device, comprising the following steps:
[0062] (1) The initial parameters of the SnSe material were imported from the Materials Studio material library. After cutting the (001) crystal plane, the minimum unit cell structure of the SnSe layer was established.
[0063] (2) After geometric optimization of the SnSe layer, the system energy and charge conditions of the SnSe layer are determined.
[0064] (3) A molecular model of the decomposition products of C4F7N gas was established, and the geometry of the decomposition products of C4F7N gas was optimized to determine the system energy, charge status, bond lengths and bond angles of each molecule of the SnSe layer.
[0065] Among them, the decomposition products of C4F7N gas include CF3CN, COF2 and C2F5CN.
[0066] (4) Geometric optimization and energy calculation of the single-chain adsorption structure of C4F7N gas decomposition products.
[0067] (5) Construct the calculation functions of the adsorption energy, doping energy and charge transfer amount of the SnSe layer, and define the required calculation formulas and physical quantities.
[0068] Select the generalized gradient approximation GGA and PBE function, and establish a SnSe layer containing 18 Sn atoms and 18 Se atoms. The size of the vacuum layer is Considering the static electronic structure, the atomic orbital basis set is set to double numerical plus polarization (DNP) and the self-consistent ring energy is 10 -6 Ha, the global orbital cutoff radius is
[0069] (6) Set the parameters of the custom adsorption calculation formula and construct a density functional theory calculation model of SnSe based on a 7×7×1 Monkhorst-Pack k-point grid.
[0070] Based on density functional theory and first principles, Grimme correction rule was used to correct van der Waals forces and long-range interactions. To avoid nuclear relativistic effects, DFT functional semi-nuclear pseudopotential (DSSP) was used. In the geometry optimization and electronic property convergence analysis, a 7×7×1 Monkhorst-Pack k-point grid was used, and the electronic energy self-consistent accuracy, maximum stress accuracy, and displacement accuracy were set to 10, respectively. -6 Ha, and
[0071] (7) The adsorption models of C4F7N gas decomposition products were established at the top, hole and bridge positions of Sn and Se atoms on the surface of SnSe layer, and the distance between C4F7N gas decomposition products and SnSe layer was controlled within Then, according to the overall energy and charge transfer of each adsorption structure, combined with the custom adsorption calculation formula, the SnSe-based composite adsorption structure with the smallest SnSe layer deformation, the largest charge transfer amount and the largest adsorption energy for different targeting molecules was found.
[0072] The adsorption energy calculation formula of the C4F7N gas decomposition product on the SnSe layer is:
[0073] E Ads =E Gas / SnSe -E SnSe -E Gas .
[0074] Among them, E Gas / SnSe is the energy of the decomposition product of C4F7N gas adsorbed by the SnSe layer, E SnSe is the energy of the SnSe layer, E Gas is the energy of the decomposition product of a single C4F7N gas.
[0075] Charge transfer amount of SnSe adsorption system
[0076] Q Tra =Q a -Q b .
[0077] Among them, Q a is the charge carried by the SnSe layer after adsorbing the decomposition product of C4F7N gas, Q b is the charge carried by the SnSe layer before adsorbing the decomposition products of C4F7N gas.
[0078] (8) The density of states of the decomposition products of SnSe and C4F7N gases were derived and analyzed. Then, the conductivity of the adsorption system was analyzed based on the integral and variation degree of the energy curve near the Fermi level.
[0079] (9) Calculate the change in the work function of the SnSe adsorption system in the decomposition products of C4F7N gas.
[0080] The formula used to calculate the change in the work function of the SnSe adsorption system in the C4F7N gas decomposition product is:
[0081]
[0082] Among them, E vacuum is the potential away from the surface of the SnSe layer, and E fermi is the energy of the highest occupied state in the system.
[0083] (10) The recovery time τ is used to evaluate the ability of SnSe materials to desorb gas, which is used to evaluate the effectiveness of high-voltage insulation devices and to evaluate the gas sensing ability of the SnSe layer.
[0084] The calculation formula of recovery time τ is:
[0085] τ=v0 -1 exp(-E a / kT).
[0086] Among them, v0 -1 is the trial frequency, which is 10 12 s -1 ; k is 1.38×10 -23 J / K; T is the actual temperature, the unit is K.
[0087] Figure 1 The front and left views of the SnSe layer after 7×7×1 Monkhorst-Pack k-point mesh geometry optimization are shown. The left view is the front view, and the right view is the left view. Figure 1 It can be seen that the bond lengths of Sn-Se bonds in the horizontal and vertical directions are and A single unit cell is a planar single-layer repeating structure with high symmetry.
[0088] Figure 2 The geometric model of the SnSe layer after adsorbing the decomposition products of C4F7N gas is shown. It can be seen from the figure that as the adsorption process is completed, the SnSe layer will undergo different degrees of deformation. It can be observed that the gas adsorption distance of the SnSe layer is greater than The longer adsorption distance means that there is a weaker interaction between the SnSe material and the gas molecules, thus showing a smaller level of charge transfer. F atoms play a leading role in the adsorption process due to their higher electronegativity and polarity. During the adsorption process, the three gas molecules all act as electron acceptors to obtain electrons from the SnSe material. The adsorption performance of the three gas molecules is ranked as follows: CF3CN>COF2>C2F5CN.
[0089] In another specific embodiment, the present invention further provides a method for evaluating the insulation properties of C4F7N gas in a high-voltage insulation device, comprising the following steps:
[0090] (1) The initial parameters of the SnSe material were imported from the Materials Studio material library. After cutting the (001) crystal plane, the minimum unit cell structure of the SnSe layer was established.
[0091] (2) After the geometry of the SnSe layer is optimized, a Sn on the surface of the SnSe layer is firstly removed to form a vacancy structure and then the geometry is optimized, and then the system energy and charge of the SnSe layer are determined.
[0092] (3) A molecular model of the decomposition products of C4F7N gas was established, and a molecular model of a single Ni atom was established. The geometric optimization of the decomposition products of C4F7N gas and the single Ni atom was performed to determine the system energy, charge status, bond lengths and bond angles of each molecule of the SnSe layer.
[0093] Among them, the decomposition products of C4F7N gas include CF3CN, COF2 and C2F5CN.
[0094] (4) Geometric optimization and energy calculation of the single-chain adsorption structure of C4F7N gas decomposition products.
[0095] (5) Construct the calculation functions of the adsorption energy, doping energy and charge transfer amount of the SnSe layer, and define the required calculation formulas and physical quantities.
[0096] Select the generalized gradient approximation GGA and PBE function, and establish a SnSe layer containing 18 Sn atoms and 18 Se atoms. The size of the vacuum layer is Considering the static electronic structure, the atomic orbital basis set is set to double numerical plus polarization (DNP) and the self-consistent ring energy is 10 -6 Ha, the global orbital cutoff radius is
[0097] (6) Set the parameters of the custom adsorption calculation formula and construct a density functional theory calculation model of SnSe based on a 7×7×1 Monkhorst-Pack k-point grid.
[0098] Based on density functional theory and first principles, Grimme correction rule was used to correct van der Waals forces and long-range interactions. To avoid nuclear relativistic effects, DFT functional semi-nuclear pseudopotential (DSSP) was used. In the geometry optimization and electronic property convergence analysis, a 7×7×1 Monkhorst-Pack k-point grid was used, and the electronic energy self-consistent accuracy, maximum stress accuracy, and displacement accuracy were set to 10, respectively. -6 Ha, and
[0099] (7) placing the geometrically optimized single Ni atom at a Sn vacancy in the SnSe layer to form a Ni-SnSe layer, and then re-optimizing the geometry of the Ni-SnSe layer;
[0100] (8) The adsorption models of C4F7N gas decomposition products were established at the top, hole and bridge positions of Sn and Se atoms on the surface of Ni-SnSe layer, and the distance between C4F7N gas decomposition products and Ni-SnSe layer was controlled within Then, according to the overall energy and charge transfer of each adsorption structure, combined with the custom adsorption calculation formula, the Ni-SnSe-based composite adsorption structure with the smallest Ni-SnSe layer deformation, the largest charge transfer amount and the largest adsorption energy for different targeting molecules was found.
[0101] The adsorption energy calculation formula of the C4F7N gas decomposition product on the Ni-SnSe layer is:
[0102] E Ads =E Gas / Ni-SnSe -E Ni-SnSe -E Gas .
[0103] Among them, E Gas / Ni-SnSe is the energy of the decomposition product of C4F7N gas adsorbed on the Ni-SnSe layer, E Ni-SnSe is the energy of the Ni-SnSe layer, E Gas is the energy of the decomposition product of a single C4F7N gas.
[0104] The calculation formula of charge transfer amount of Ni-SnSe adsorption system is:
[0105] Q Tra =Q a -Q b .
[0106] Among them, Q a is the charge carried by the Ni-SnSe layer after adsorbing the decomposition products of C4F7N gas, Q bis the charge carried by the Ni-SnSe layer before adsorbing the decomposition products of C4F7N gas.
[0107] (8) The density of states of the decomposition products of Ni-SnSe and C4F7N gases were derived and analyzed. Then, the conductivity of the adsorption system was analyzed based on the integral and variation degree of the energy curve near the Fermi level.
[0108] (9) Calculate the change in work function of the Ni-SnSe adsorption system in the decomposition products of C4F7N gas.
[0109] The formula used to calculate the change in the work function of the Ni-SnSe adsorption system in the C4F7N gas decomposition product is:
[0110]
[0111] Among them, E vacuum is the potential away from the surface of the Ni-SnSe layer, and E fermi is the energy of the highest occupied state in the system.
[0112] (10) The recovery time τ is used to evaluate the ability of Ni-SnSe materials to desorb gas, which is used to evaluate the effectiveness of high-voltage insulation devices and to evaluate the gas sensing capability of the Ni-SnSe layer.
[0113] The calculation formula of recovery time τ is:
[0114] τ=v0 -1 exp(-E a / kT).
[0115] Among them, v0 -1 is the trial frequency, which is 10 12 s -1 ; k is 1.38×10 -23 J / K; T is the actual temperature, the unit is K.
[0116] Figure 4 The main view and left view of the Ni-SnSe layer after 7×7×1 Monkhorst-Pack k-point mesh geometry optimization. The left picture is the main view, and the right picture is the left view. Figure 4 It can be seen that the Ni-SnSe material undergoes geometric deformation after geometry optimization. This is because the strong metallicity of the transition metal Ni atom activates the SnSe material, causing the Sn-Se bonds near the Ni atom to stretch. The A bond, B bond, and C bond (A, B, and C are custom-defined to distinguish the different bonds that form bonds with the doped atoms) are changed to and Moreover, the E Dop(doping energy) is -6.294eV. The higher doping energy means that a more intense interaction occurs between Ni atoms and SnSe materials. In addition, Q Tra (Charge transfer amount) is 0.064e, which further confirms that Ni atoms can act as electron donors to transport electrons to SnSe materials, proving the success of the process of transition metal Ni atoms modifying Sn vacancy SnSe layer.
[0117] Figure 5 The geometric model of Ni-SnSe layer after adsorption of C4F7N gas decomposition products. It can be seen from the figure that the gas molecules deformed before and after adsorption. This is due to the chemical adsorption between Ni-SnSe layer and gas molecules. The adsorption effect is more obvious, and the adsorption energy of various C4F7N gas decomposition products increased by 76.5%, 65.8% and 55.8% respectively. In addition, the interaction between C atoms and Ni atoms is more obvious during the adsorption process. Therefore, in the three adsorption configurations, C atoms and Ni atoms are significantly close, and the adsorption distance is significantly reduced. Ni-SnSe layer still acts as an electron donor in the adsorption process of CF3CN, COF2 and C2F5CN, and the electron transfer capacity of Ni-SnSe layer is significantly higher than that of SnSe layer. The charge transfer amount becomes 13.13 times, 15.16 times and 11.19 times respectively. This is because the transition metal Ni atom can improve the band structure of SnSe layer, thereby reducing the energy required for electron transmission.
[0118] Figure 6 The density of states distribution diagram of the decomposition products of C4F7N gas adsorbed on SnSe layer and Ni-SnSe layer respectively is shown, where the dotted line is the Fermi level. The energy distribution level of the Fermi level largely determines the sensing sensitivity and conductivity of the sensing system. As can be seen from the figure, the SnSe layer has obvious energy distribution at -1.5eV, -2.7eV and -7eV. For the Ni-SnSe layer, the energy distribution of each energy level has shifted to the side close to the Fermi level, which means that electrons can occupy more intervals near the Fermi level, and then the large electronic state can promote the conductivity of the doped system and make the system more potential for adsorption sensing. At the same time, it can be observed that there is a significant overlap of energy peaks between gas molecules and adsorbed substrates near the Fermi level. This is because the outermost orbit of the gas molecule and the outermost orbit of the adsorbed substrate are highly hybridized, which shows that the position of the energy peak is the same.
[0119] Figure 7The work function change curves of the SnSe layer and the Ni-SnSe layer in the C4F7N gas decomposition products are shown. It can be seen from the figure that after the Ni atom doping process of the SnSe layer is completed, the work function energy of the Ni-SnSe system is further reduced, which means that the energy required for electrons to cross energy levels is reduced, that is, the conductivity of the Ni-SnSe system increases and the resistance decreases, making the Ni-SnSe material more potential for gas sensing. With the completion of the gas adsorption process, the work functions of the SnSe adsorption system and the Ni-SnSe adsorption system further increase and show the same change trend. Compared with the SnSe adsorption system, the rate of change of the work function of the Ni-SnSe adsorption system after adsorbing the C4F7N gas decomposition products is higher.
[0120] Figure 3 and Figure 8 The schematic diagrams of the theoretical recovery time of SnSe layer and Ni-SnSe layer in the adsorption process of C4F7N gas decomposition products are shown respectively. It can be seen from the figure that the gas theoretical recovery time shown by SnSe layer adsorption is of a lower order of magnitude, which means that the gas has been desorbed before it is completely adsorbed, which is not easy to collect and analyze the actual sensing electrical signal. However, by using Ni-SnSe layer adsorption, it can be observed that under normal temperature (298K) working conditions, the response recovery time of C4F7N gas decomposition products has been significantly improved, which is related to the improvement of the surface active sites of the sensing material and the material structure and morphology. Therefore, Ni-SnSe material can be used as a good sensing material and then applied to the reliable detection of CF3CN, COF2 and C2F5CN.
[0121] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for evaluating the insulation properties of C4F7N gas in a high-voltage insulation device, characterized in that: The following steps are involved: (1) Import the initial parameters of SnSe material from the Materials Studio material library, and establish the minimum unit cell structure of the SnSe layer after cutting the (001) crystal plane; (2) After geometric optimization of the SnSe layer, the system energy and charge of the SnSe layer are determined; (3) Establish a molecular model of the decomposition products of C4F7N gas, and perform geometric optimization on the decomposition products of C4F7N gas to determine the system energy, charge, bond length and bond angle of each molecule of the SnSe layer; (4) Geometry optimization and energy calculation of the single-chain adsorption structure of C4F7N gas decomposition products; (5) Construct the calculation function of the adsorption energy, doping energy and charge transfer amount of the SnSe layer, and define the required calculation formulas and physical quantities; (6) Setting the parameters of the custom adsorption calculation formula and constructing a density functional theory calculation model of SnSe based on a 7×7×1 Monkhorst-Packk point grid; (7) The adsorption models of C4F7N gas decomposition products were established at the top, hole and bridge positions of Sn atoms and Se atoms on the surface of the SnSe layer. Then, according to the overall energy and charge transfer of each adsorption structure, the SnSe-based composite adsorption structure with the smallest deformation of the SnSe layer, the largest charge transfer amount and the largest adsorption energy for different target molecules was found in combination with a custom adsorption calculation formula; (8) The density of states of the decomposition products of SnSe and C4F7N gas was derived and analyzed, and then the conductivity of the adsorption system was analyzed based on the integral and change degree of the energy curve near the Fermi level; (9) Calculate the change in work function of SnSe adsorption system in C4F7N gas decomposition products; (10) The recovery time τ is used to evaluate the ability of SnSe materials to desorb gas, which is used to evaluate the effectiveness of high-voltage insulation devices and to evaluate the gas sensing ability of the SnSe layer.
2. The insulation property evaluation method according to claim 1, characterized in that: After the geometry optimization of the SnSe layer in step (2), a Sn on the surface of the SnSe layer is firstly removed to form a vacancy structure and then the geometry optimization is performed, and then the system energy and charge of the SnSe layer are determined.
3. The insulation property evaluation method according to claim 2, characterized in that: In step (3), while establishing the molecular model of the decomposition product of C4F7N gas, a model of a single transition metal atom is also established; When the geometry optimization of the C4F7N gas decomposition product is performed in step (3), the geometry optimization of the single transition metal atom is also performed.
4. The insulation property evaluation method according to claim 3, characterized in that: The transition metal atoms include Ni atoms.
5. The insulation property evaluation method according to claim 4, characterized in that: Between step (6) and step (7), the following steps are performed: The geometrically optimized single Ni atom is placed at a Sn vacancy of a SnSe layer to form a Ni-SnSe layer, and then the Ni-SnSe layer is geometrically optimized again.
6. The insulation property evaluation method according to any one of claims 1 to 5, characterized in that: The decomposition products of the C4F7N gas in step (3) include CF3CN, COF2 and C2F5CN.
7. The insulation property evaluation method according to any one of claims 1 to 6, characterized in that: When the adsorption model of the C4F7N gas decomposition product is established in step (7), the distance between the C4F7N gas decomposition product and the SnSe layer is controlled within 8. The insulation property evaluation method according to any one of claims 1 to 7, characterized in that: After step (7), the adsorption energy calculation formula of the C4F7N gas decomposition product on the SnSe layer is obtained: AND Ads =And Gas / SnSe -AND SnSe -AND Gas ; Among them, E Gas / SnSe is the energy of the decomposition product of C4F7N gas adsorbed by the SnSe layer, E SnSe is the energy of the SnSe layer, E Gas is the energy of the decomposition product of a single C4F7N gas.
9. The insulation property evaluation method according to any one of claims 1 to 8, characterized in that: After step (7), the charge transfer amount Q of the SnSe adsorption system is obtained. Tra =Q a -Q b ; Among them, Q a is the charge carried by the SnSe layer after adsorbing the decomposition product of C4F7N gas, Q b is the charge carried by the SnSe layer before adsorbing the decomposition products of C4F7N gas.
10. The insulation property evaluation method according to any one of claims 1 to 9, characterized in that: The formula used in step (9) to calculate the change in the work function of the SnSe adsorption system in the C4F7N gas decomposition product is: Among them, E vacuum is the potential away from the surface of the SnSe layer, and E fermi is the energy of the highest occupied state in the system; Preferably, the calculation formula of the recovery time τ in step (10) is: τ=v0 -1 exp(-E a / kT); Among them, v0 -1 is the trial frequency, which is 10 12 s -1 ; k is 1.38×10 -23 J / K; T is the actual temperature, the unit is K.
Citation Information
Patent Citations
Method for calculating spatial distribution condition of discharge decomposition products of high-voltage electrical equipment
CN110910968A
High-voltage electrical equipment insulation strength calculation method based on gas decomposition product
CN111308279A
Method for evaluating compatibility of novel environment-friendly insulating gas and solid material in equipment
CN113759081A
Screening method for adsorbent in environment-friendly gas-insulating equipment
US20230081241A1
Cited By
Evaluation and calculation method for compatibility between environment-friendly insulating gas and metal electrode discharge
CN121354699A